2019
DOI: 10.1177/2309499019847815
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar hemiarthroplasty using microarc oxidation-coated cementless stem in patients with unstable intertrochanteric fracture

Abstract: Purpose: Treatment for an unstable intertrochanteric fracture in elderly patients is challenging. Bipolar hemiarthroplasty (HA) using microarc oxidation (MAO) coating has been a treatment option alternative to internal fixation. However, the outcome of bipolar HA using MAO-coated stem in these patients is unknown. Methods: From July 2007 to April 2016, 234 (older than 65 years) patients (234 hips) who were diagnosed as having unstable intertrochanteric fractures were treated with bipolar HA using a fully MAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Recently, the cementless stem has been widely used for hip arthroplasty and there have been many studies reporting good results for unstable intertrochanteric fractures [3][4][5][6][7][8][9]. However, studies evaluating the long-term outcomes patients who have survived for over five years or femoral stems applied using different fixation methods according to each design have been small studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the cementless stem has been widely used for hip arthroplasty and there have been many studies reporting good results for unstable intertrochanteric fractures [3][4][5][6][7][8][9]. However, studies evaluating the long-term outcomes patients who have survived for over five years or femoral stems applied using different fixation methods according to each design have been small studies.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, if the type 3C stem is used for intertrochanteric fractures in which the proximal region is fractured, the bone ongrowth of the proximal region may be poorer because the fixation force is mainly obtained in the diaphysis and stable three-point fixation cannot be achieved. Some studies have reported good results with type 3C stems for unstable intertrochanteric fractures [3,7]. However, studies that report excellent results using these type 3C stems have been mostly short-term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical approach to CFFs has gained clarity in the literature [12], while surgical indication in ITFs is still controversial [13]. While many surgeons always prefer osteosynthesis in ITF, many surgical teams prefer hemiarthroplasty [14].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the hip arthroplasty for this fracture may lead to a stable outcome regarding functional recovery and pain relief by devising a speci c surgical procedure [5,6]. However, the hip arthroplasty was applied through the posterior approach in many reports, for which large surgical stress is of concern, the risk of dislocation is high, and osteosynthesis is additionally applied to the greater trochanter [7][8][9]. Recently, the direct anterior approach (DAA) for applying the hip arthroplasty has been attracting attention as an approach capable of conservation of soft tissue, which enables early functional recovery and a low dislocation rate [10][11][12].…”
Section: Introductionmentioning
confidence: 99%